2021
DOI: 10.3389/fmicb.2021.646748
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Divalent Cations (Cu, Zn, Pb, Cd, and Sr) on Microbially Induced Calcium Carbonate Precipitation and Mineralogical Properties

Abstract: Microbially induced calcium carbonate precipitation (MICP) is a bio-geochemical process involving calcium carbonate precipitation and possible co-precipitation of other metals. The study investigated the extent to which a urease-positive bacterium, Sporosarcina pasteurii, can tolerate a range of metals (e.g., Cu, Zn, Pb, Cd, and Sr), and analyzed the role of calcium carbonate bioprecipitation in eliminating these divalent toxicants from aqueous solutions. The experiments using S. pasteurii were performed aerob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…These values are insufficient to support a potential application in a mining operation, where the removal of metals should be significant to justify the investment. Reports have shown low copper removals at copper concentrations over 0.5 mM and, on the contrary, high copper removals at lower copper concentrations [28,46].…”
Section: Copper Removalmentioning
confidence: 99%
“…These values are insufficient to support a potential application in a mining operation, where the removal of metals should be significant to justify the investment. Reports have shown low copper removals at copper concentrations over 0.5 mM and, on the contrary, high copper removals at lower copper concentrations [28,46].…”
Section: Copper Removalmentioning
confidence: 99%
“…Conversely, the formation of brushite was associated with significantly lower heavy metal removal efficiency of those heavy metals. Recent reports demonstrated that divalent heavy metals can interact with MICP [ 23 , 47 ]. It also has been shown that heavy metals such as cadmium, cobalt, nickel, zinc may alter the calcite dissolution process [47] .…”
Section: Discussionmentioning
confidence: 99%
“…It also has been shown that heavy metals such as cadmium, cobalt, nickel, zinc may alter the calcite dissolution process [47] . The incorporation of these heavy metals results in inhibition or enhancement of the solubility of calcite, depending on the type of metals and their content [23] . The formation of chromium oxide (Cr 2 O 3 ) in the Pseudomonas aeruginosa (QD5 & QZ9) UM-Cr cultures were combined with 100% of removal efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, a biomineralization reaction induced by S. pasteurii cells could provide sufficient CO 3 2− ions to integrate these metal cations into undissolving carbonate for easy removal (Figure 4D) [82]. Soils contaminated with strontium (Sr) or lead (Pb) were successfully removed by biomineralization of S. pasteurii cells with more than 99% efficiency [83]. Recently, multiple heavy metals, such as cadmium (Cd), zinc (Zn) and copper (Cu), were also reported to be eliminated from soils using biomineralization technology [84,85].…”
Section: Environmental Applicationsmentioning
confidence: 99%